OPEN REPAIR OF PARAOESOPHAGEAL HERNIA–IS THERE STILL A ROLE?. (8th June 2013) - Burnside, N; Mhandu, P; d'Silva, C; McGuigan, J; McGonigle, N
Abstract : Introduction: Laparoscopy has become the standard repair in paraesophageal hernias as it is safe, with good symptomatic control. However several reports have demonstrated recurrence rates as high as 42%. This high recurrence rate has led us to question whether this procedure is more advantageous than the tradition open approach particularly in the elderly patient in whom reoperation at a later date may not be an option. Aims/Background: The subgroup of multiple co-morbidity patients, present a specific problem, as many that might tolerate the laparoscopic approach would present significant risk when dealing with symptoms as a result of procedural failure. We questioned whether open gastropexy with or without antireflux procedure might be beneficial in these patients. Method: This study looked at our recent experience with paraoesophageal hernia repair using a small upper midline laparotomy. Forty patients, 9 male and 31 female, underwent a reduction of hernia, crural repair, and either anterior gastropexy or antireflux procedure.We elected not to resect the peritoneal hernial sac. All patients were followed up for recurrence of their symptoms and hernia. Results: Mean age of 63 years (27–82 years) 50%. All patients had significant co-morbidity and half of the patients (20/40) had a significantly limited exercise tolerance preoperatively, with one patient critically unwell and ventilated. Two patients developed a recurrence of their hernia (5%), one at day two post operatively and the other seven years post operatively following a road traffic collision. Operative mortality was 5% (2/40), the first patient was ventilator dependent in Intensive Care preoperatively and the procedure was performed to assist with ventilator weaning. The second patient died at home suddenly following discharge, post-mortem was non diagnostic. Conclusion: Symptom control was excellent with only one patient (2.5%) developing recurrence of symptoms post operatively. The higher rate of recurrence demonstrated in laparoscopic surgery is not mirrored in open surgery. We believe these data demonstrate potentially superior results when performing open repair in higher risk patients.